2018
DOI: 10.3329/jbau.v16i3.39393
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing rice yield in acidic soil through liming and fertilizer management

Abstract: The effect of lime and fertilizer application, as the management of soil acidity, on the growth and yield of rice cv. BRRI dhan50 was investigated during Aman rice season at the Agronomy Field Laboratory of Sylhet Agricultural University, Bangladesh. The experiment was consisted of two factors namely lime and fertilizer. There were four levels of lime (0, 0.50, 1.00, and 1.50 t ha–1 of CaCO3.MgCO3) and three levels of fertilizers (control, FYM @ 10 t ha–1, and chemical fertilizer @ 100-30-42-4-3-0.4 kg ha–1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(36 reference statements)
5
5
0
2
Order By: Relevance
“…These results indicate that lime application had a positive effect on filled grain which ultimately produced a higher yield. These observations agree with the findings of Ferdous et al (2018).…”
Section: Yield Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicate that lime application had a positive effect on filled grain which ultimately produced a higher yield. These observations agree with the findings of Ferdous et al (2018).…”
Section: Yield Parameterssupporting
confidence: 93%
“…The positive effects of liming on crops have been reported to increase plant height in acidic soil. The work done by Alfaons et al (2008) and Ferdous et al (2018) was found to be in conformity with the above observation. The increase in plant height might be owing to reduced loss of nutrients by fixation of NH 4+ ion with humus present in FYM and increased availability to crop which ultimately increased the plant height.…”
Section: Growth Parameterssupporting
confidence: 84%
See 1 more Smart Citation
“…Compared to the control treatment, application of locally recommended NP nutrients increased number of effective tillers by 68.6% (Table 3). Similar result was reported by Ferdous et al (2018). Increased effective tiller production of NPKSZn compared to the recommended NP and NPK can be attributed to the ability of Zn to increase N use efficiency and Zn induced enzymatic activity as well as auxin metabolism in plants (Arif et al, 2018;Rana and Kashif, 2014).…”
Section: Number Of Effective Tillerssupporting
confidence: 77%
“…Soil acidity (low pH) is a limiting factor in rice [14] and maize production. The results showed that low soil pH had an impact on reducing maize yields by 11-37% [15], and rice yields from 14.52-28.97% [16]. Rice productivity in acid soils can be increased, among others, through the application of lime [17], and the application of Ground Magnesium Limestone (GML) in combination with a biofertilizer [13].…”
Section: Introductionmentioning
confidence: 99%